Factors Affecting the Quality of Education at Primary School Level - Fatima, Sardar; Javaid, Bisma; Malik, Muhammad Shafi (Annals of Human and Social Sciences, 2023)
The purpose of this study was to explore the factors affecting the quality of education at primary school level. These factors include qualified and well-trained teachers, curriculum and teaching material, attendance and class size, teacher-student ratio, parental and community involvement, socioeconomic and cultural background, teacher training and professional development, and educational policies. This study was also aimed at investigating the teachers' views about the reasons for these factors and to find out how these factors may be solved. The quantitative research method was used for this study. A questionnaire composed on 40 close-ended statements was developed on a five-point Likert scale. A convenient sampling technique was used to select the sample of 300 teachers from the Lahore district. The data was analyzed using descriptive and inferential statistics and an independent t-test was used through SPSS to find out the difference between genders’ views. The findings of the study indicate that these factors exist and have a great affect on the quality of education at the primary school level. It is highly recommended that continuous professional development programs must be start at primary school level on regular basis to enhance the teaching skills of teachers.